2020
DOI: 10.1080/10255842.2020.1737027
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of segmental lumbar lordosis and risk of cage subsidence with different cage heights and alternative placements in transforaminal lumbar interbody fusion

Abstract: Biomechanical analysis of segmental lumbar lordosis and risk of cage subsidence with different cage heights and alternative placements in transforaminal lumbar interbody fusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In the MCBT-TT group, the intervertebral disc stress was more dispersed and lower, with the least stress in rotation (3.48 ± 0.57 Mpa). Rastegar et al ( 31 ) demonstrated that cage subsidence was one of the risk factors for failure of lumbar interbody fusion. With the increase of cage stress, subsidence rate increased gradually ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the MCBT-TT group, the intervertebral disc stress was more dispersed and lower, with the least stress in rotation (3.48 ± 0.57 Mpa). Rastegar et al ( 31 ) demonstrated that cage subsidence was one of the risk factors for failure of lumbar interbody fusion. With the increase of cage stress, subsidence rate increased gradually ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…They effectively reduced the lateral stress of the intervertebral disc in lateral bending (TT-TT: 9.288 ± 0.395 MPa, CBT-CBT: 8.303 ± 0.370 MPa, CBT-TT: 6.080 ± 0.443 MPa, TT-CBT: 6.413 ± 0.513 MPa), and the intervertebral disc stress was concentrated in the central part in rotation, while at the same time, stress of the edge was dispersed (Figures 6(a) and 6(b) ). Rastegar et al [ 36 ] reported in a previous biomechanical study that cage subsidence has also been shown to be an important risk factor after lumbar interbody fusion. Lower cage stress might be obtained when decompression and fusion at the responsible stage is performed with the hybrid technique.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, the footprint of cages in OLIF is at least twice the size of that in MIS-TLIF and is wide enough to stand on both sides of the dense peripheral apophyseal bone [ 56 – 59 ]. Biomechanical analysis has also suggested that such constructs may effectively diminish stress peaks and disperse the stress in the endplate cancellous bone equally, which is beneficial for both fusion and subsidence resistance [ 60 62 ].…”
Section: Discussionmentioning
confidence: 99%